2008
DOI: 10.3748/wjg.14.4324
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ethanol on insulin-like growth factor-I system in primary cultured rat hepatocytes: Implications of JNK1/2 and alcoholdehydrogenase

Abstract: AIM:To evaluate the effects of ethanol on the insulinlike growth factor-Ⅰ (IGF-Ⅰ) system involved in c-Jun N-terminal kinase (JNK1/2) and alcoholdehydrogenase (ADH) activity in primary cultured rat hepatocytes. M E T H O D S : H e p a t o c y t e s i s o l a t e d f r o m m a l eSprague-Dawley rats were incubated with various concentrations of ethanol for different durations of time. The cells were pretreated with SP600125 (10 μmol/L) and 4-MP (200 μmol/L), and then treated with ethanol (200 mmol/L). We then m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…It is tempting to speculate that the JNK2/3 and ERK2 might constitute 2 consecutive signaling events in the cellular pathway involved in the ACA‐dependent pressor effect of EtOH, with the phosphorylation of JNK2/3 leading to downstream ERK activation. Along the same cascade, recent evidence suggests a facilitatory role for alcohol dehydrogenase in the EtOH‐evoked JNK phosphorylation (Oh et al., ) in addition to its established role in EtOH metabolism (Quertemont et al., ). Notably, the oxidative catabolism of EtOH into ACA by alcohol dehydrogenase/catalase mediates the pressor action of intra‐RVLM EtOH in SHRs (El‐Mas and Abdel‐Rahman, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is tempting to speculate that the JNK2/3 and ERK2 might constitute 2 consecutive signaling events in the cellular pathway involved in the ACA‐dependent pressor effect of EtOH, with the phosphorylation of JNK2/3 leading to downstream ERK activation. Along the same cascade, recent evidence suggests a facilitatory role for alcohol dehydrogenase in the EtOH‐evoked JNK phosphorylation (Oh et al., ) in addition to its established role in EtOH metabolism (Quertemont et al., ). Notably, the oxidative catabolism of EtOH into ACA by alcohol dehydrogenase/catalase mediates the pressor action of intra‐RVLM EtOH in SHRs (El‐Mas and Abdel‐Rahman, ).…”
Section: Discussionmentioning
confidence: 99%
“…1). To analyze resistance and growth in response to RA, cell viability was determined using MTT methods [27,28]. As shown in figure 1a, treatment with RA at 10 –10 to 10 –7 M inhibited cell viability in a dose-dependent manner, with inhibition being significant at 10 –7 M compared with untreated controls (p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, IGF-I signal transduction pathways, such as those involving insulin receptor substrate 1 (IRS-1) and MAPK/ERK, have signaling cascades that involve Shc, ErbB2 and Sos [25]. We recently reported that the ethanol-induced inhibitory effect of IGF-I is related to actions of p42/44 MAPK [26] and p54/46 SAPK/JNK [27] in rat hepatocytes. One of the downstream signaling molecules of IGF-I receptor, IRS-1, is expressed in human breast cancer, and a high level of IRS-1 expression is an indicator of early disease recurrence in small tumors [28].…”
Section: Introductionmentioning
confidence: 99%
“…These findings correlated with an increase in hepatic triglycerides, suggesting a possible mechanism for the clinically observed fatty liver. Chronic ethanol treatment in isolated hepatocytes has also been shown to impair hepatic triglyceride lipase secretion, while both acute and chronic treatment impairs IGF-1 secretion, the latter of which is prevented by the addition of 4-MP [64,67,113]. Also, studies examining transferrin processing and secretion noted increased hepatic transferrin in the Golgi of both rats and humans with alcoholic liver disease [2,[47][48][49].…”
Section: Other Secreted Moleculesmentioning
confidence: 99%